Chest Pain from Pneumopericardium with Gastropericardial Fistula - Abdullah Rathur; Hussein Al-Mohamad; Jeffrey Steinhoff; Ronald Walsh (Case Reports in Cardiology)
Introduction. Gastropericardial fistula, a connection between the upper gastrointestinal tract and pericardium, is a rare clinical finding most commonly associated with postsurgical complications, as well as direct tissue invasion from gastric cancer. Case Report. We report a case of a 58-year-old Caucasian woman with metastatic colon cancer treated with FOLFOX, a combination chemotherapy regimen, and bevacizumab who presented with chest pain. She was ruled out for acute coronary syndrome, aortic dissection, or pulmonary embolism. A computed tomography (CT) scan of her chest showed pneumopericardium. A barium swallow ruled out esophageal ulceration, and esophagogastroduodenoscopy (EGD) showed a large penetrating gastric ulcer with no evidence of gastric dysplasia or malignancy or evidence of Helicobacter pylori (H. pylori). The patient underwent median sternotomy with gastric ulcer resection and repair, as well as pericardial washout and pericardial chest tube placement. After an uncomplicated course, she was safely discharged home. Conclusion. Given that gastrointestinal ulceration and perforation are known phenomena in patients taking vascular endothelial growth factor (VEGF) inhibitors, surveillance endoscopy may be beneficial to discover them before they result in potentially fatal complications such as gastropericardial fistulas.